Obstacles to developing the university curriculum for active learning: A field study on a sample of university professors (Journal of the College of Basic Education, 2024)
Through the current study, we seek to clarify the nature of the obstacles that hinder the development of the university curriculum for active learning through a field study on a sample of university professors amounting to (100) individuals. The researcher was keen to select them randomly according to a number of variables. To collect data and information, a questionnaire was designed with a set of Dimensions: The researcher verified the validity and reliability tests of the questionnaire. After that, the questionnaire was applied to the research sample. The study concluded the following:The questionnaire as a whole obtained an arithmetic mean of (4.15), which represents the percentage weight (83%), and therefore active learning achieved a very good level.The field of (learners) and the field of (university administration) ranked first, while the second place went to (curriculum teachers).